Varietal and harvesting time effects on physical characteristics and sensory properties of roasted fresh yellow maize hybrids - Alamu, Emmanuel Oladeji; Bussie, M.D.; Olorunfemi, O.; Abebe, M. (IOSR Journals, 2015)
The present study evaluated the effects of physical characteristics and harvesting time on the overall likeness of roasted fresh yellow maize hybrids. Freshly harvested cobs from eight biofortified yellow maize hybrids, at three harvesting time (20, 27 and 34 days after pollination (DAP)), were used for this study. The harvested fresh yellow maize cobs were roasted with and without intact husk on hot-charcoal burning on wire gauze until the seeds were cooked and turned brown. Sensory evaluation was carried out on the roasted fresh yellow maize samples within 24 hours after harvesting. The physical characteristics of the fresh maize grains were also determined. Variety and harvesting time had significant effects (P?0.001) on most of the physical properties, except porosity. Harvesting time and husk had effects on the overall likeness of roasted maize hybrids with husk or without husk. The optimum harvesting time to consume roasted maize hybrids was found to be 20DAP, but the overall likeness rating for roasted fresh yellow maize hybrid without husk was higher than that of roasted fresh yellow maize hybrid with husk. There was negative but significant correlation between the physical characteristics and the sensory properties except colour that showed positive correlation. Differences in kernel characteristics caused by genetic inheritance and harvesting time can influence the processing, utilization and consumer overall likeness of maize.